Development of Educational Monopoly Learning Media in Science Subjects to Improve Students Learning Outcomes - Kamelia, Fiki; Wulandari, Desi (Postgraduate, University of Mataram, 2024)
Student interest in learning will increment in the event that the educator utilizes different learning media than expected. This research and development mean to develop and test the feasibility, and effectiveness of educational monopoly learning media in grade V elementary school science subjects. This study used the Borg and Gall model. Data collection techniques use tests (pretest-posttest) and non-tests in the form of observations, questionnaire interviews, and document data. The results of validation by media and material experts show that the media has met the very valid criteria with percentages of 88.69% and 93.33% respectively. Based on thes results pretest-posttest, is known that educational monopoly learning media is effective in improving learning outcomes, shown by the results of an increase in the average pretest score of 54.67 to 80.33 at the time of the posttest and the results of the N-Gain test obtained a value of 0.58 with the medium classification. In light of the aftereffects of the questionnaire, the response of teachers and students received a very positive response. So, it can be concluded that the educational monopoly learning media is effective in improving science learning outcomes and is suitable for use in class V learning at SDN 03 Mereng